The A to Z of vitamins, minerals, and supplements - Navarra, Tova; Shankin-Cohen, Wendy
"This accessible guide to nutritional options provides more than 900 entries that contain detailed, factual information about these substances. With a focus on how to use them safely, it discusses their effects on the body, their uses as health remedies, their risks, and the common misconceptions associated with them. Complete with appendixes listing useful resources and a handy glossary, The A to Z of Vitamins, Minerals, and Supplements, Second edition is an essential companion for anyone looking for the facts about enhancing their health with these products".--Cover.